ITER plasma source and building modelling to produce radiation maps. (27th September 2018) - Juárez, R.; Catalan, J.P.; Ogando, F.; Lopez-Revelles, A.J.; Sauvan, P.; Jakhar, S.; Polunovskiy, E.; Loughlin, M.; Sanz, J.
Abstract: The ITER Tokamak Complex is the civil structure that will host the ITER Tokamak and the largest part of the associated systems. The dimensions are 120 m  ×  80 m  ×  60 m, built mostly of concrete, with over one thousand penetrations. During ITER operation, a radiation field will spread throughout the complex from diverse radiation sources. It must be characterized to check the compliance with the limits for electronics allocation and human intervention. However, the production of radiation maps in the ITER Tokamak Complex is a task of paramount sophistication due to challenges to adequately model in MCNP the radiation sources involved. In this work, two important methodological upgrades are presented. First, a new MCNP model of the Tokamak Complex, conceived to be computationally stable while capturing a conservative representation of the baseline. Second, a novel approach to model the plasma source, called a mosaic source, allows an unprecedented degree of realism and accuracy in terms of capturing the port specificities. Both represent a step change in the capacity to produce ITER radiation maps with increased reliability, augmenting previous versions. Examples of partial radiation maps are provided considering both methodological upgrades.